Diagnostic mathematics assessment : the impact of the GIST model on learners with learning barriers in mathematics - Sekao, Rantopo David (North-West University, 2011)
Assessment, as an integral part of teaching and learning, gained unprecedented prominence in the curriculum in South Africa post 1994. When the new curriculum was introduced, it was assumed that teachers would effortlessly adapt their teaching and assessment practices, and swiftly implement the curriculum. Fourteen years after the inception of the new curriculum, majority of teachers are still grappling with issues of assessment. Previously, there was an exclusive bias towards summative assessment, which is mainly learning product-orientated and less or no focus on the other assessment typologies such as diagnostic and formative assessment, which are learning process-orientated. Of these typologies, diagnostic assessment is not being used maximally to enhance mathematics learning and inform the nature of the interventions to attend to learners' needs. The study focused on diagnostic assessment by investigating the impact of a particular model, GIST model, on the learning barriers and learner achievement in mathematics among the grade 9 learners. The investigation of the impact of the GIST model was done through the experimental design in four schools with class sizes of d > 40. Data were collected quantitatively through Study Orientation Questionnaire (SOM) and Mathematics Achievement Test (MAT) as well as qualitatively through interviews, observations and document analysis. The t-test and the analysis of covariance (ANCOVA) revealed that the GIST model improved the learner achievement practically significantly (d = 0.79). However, the GIST model could not mitigate the learning barriers and improve correlations between SOM and MAT. The study, however, does find grounds to conclude that the latter findings can be attributed to teachers' lacking understanding and implementation of diagnostic assessment, in particular the GIST components. Hence, certain recommendations are posed with regard to the applicable training of teachers in order to empower them to effectively utilize diagnostic assessment and to guide learners in overcoming learning barriers in mathematics.
Thesis (Ph.D. (Mathematics Education))--North-West University, Potchefstroom Campus, 2011.
Keywords: Diagnostic assessment; Group intervention strategy; Learning barriers; Problem solving behaviour; Mathematics anxiety; Mathematics study environment; Attitudes towards mathematics; Mathematics achievement; Leerhindernisse; Wiskundeprestasie; Probleemoplosgedrag; Wiskunde-angs; Studieomgewing; Wiskundehouding; Diagnostiese assessering